KAJIAN HUKUM NORMATIF TERHADAP SANKSI ADMINISTRASI NEGARA DALAM QANUN KOTA BANDA ACEH - Apri Rotin Djusfi (Jurnal Public Policy, 2015)
The development of Indonesia state administration law is indicated when the government manage the people by using the law order with determine the decision about prohibition  or by the issuance of permit system. Quanun based on the Law of Aceh Government is “Regulations in local regulations that rule the government administration and the society living of local area in Aceh. Generally, the type and several of sanctions is recorded and determine clearly in the administration rule. There are any sanction in administration law, i.e. government coercion, withdraw the advantage decision (subsidy permit, payment), coercion fee by government, and administration fine.  The policy on concept of administration sanction in Quanun according to the description of Act No. 11 of 2006 concerning to Aceh Government indicates that Quanun  is a rule that override  the other rules by follow the principles of Lex Specialis derogaat Lex Generalis. Asrticle 18 of Constitution of 1945 is a law base for the implementation of local autonomy by provides the local head with wide authority, real and accountable.Keyword : Development, Law, Panismen, Local Goverment